2021
DOI: 10.24908/pceea.vi0.14864
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Online Learning on Engineering Students’ Socialization Experiences During the Pandemic

Abstract: The global shift to online learning prompted by the COVID-19 pandemic has accentuated how learningonline alters postsecondary students’ socialization experiences and learning outcomes. In December 2020, alarge Canadian engineering faculty surveyed its undergraduate students to assess their learning experiences in the exclusive online environment during the pandemic. This paper used qualitative data from the survey, as complemented by descriptive quantitative results, to explore how the online environment impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In the present study, the participants reported a decrease in students' motivation and sense of belongingness to the classroom. Sweeney et al reported that anonymity in online communication may reduce students' sense of belonging [48].…”
Section: Decreased Desirable Social Learningmentioning
confidence: 99%
“…In the present study, the participants reported a decrease in students' motivation and sense of belongingness to the classroom. Sweeney et al reported that anonymity in online communication may reduce students' sense of belonging [48].…”
Section: Decreased Desirable Social Learningmentioning
confidence: 99%
“…Individual factors that influenced students' learning effectiveness during the pandemic included their digital literacies, learning habits and behaviours, including self-directed learning capabilities [14,20]. Contextual influencing factors comprised teaching methods [17], studentstudent and instructor-student interactions, course design [7,21], and unequal online access in less well-off regions [14]. These factors could also have affected the perceptions of learning effectiveness of engineering students in the context of our study.…”
Section: Learning Effectiveness During the Covid-19 Pandemicmentioning
confidence: 99%